2008
DOI: 10.1027/1618-3169.55.6.371
|View full text |Cite
|
Sign up to set email alerts
|

The Recall of Information from Working Memory

Abstract: We describe and evaluate a recall reconstruction hypothesis for working memory (WM), according to which items can be recovered from multiple memory representations. Across four experiments, participants recalled memoranda that were either integrated with or independent of the sentence content. We found consistently longer pauses accompanying the correct recall of integrated compared with independent words, supporting the argument that sentence memory could scaffold the access of target items. Integrated words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
6
27
0
Order By: Relevance
“…That is, when there were more items to remember, all responses were slowed by a roughly constant amount. This pattern has also been observed for complex span tasks (Towse, Cowan, Hitch, & Horton, 2008). In a free recall task, Rohrer (1996) showed that the time taken to recall items increased substantially when the number of items in the study list increased from 8 to 16 words.…”
Section: Benchmarks For Working Memory 19supporting
confidence: 61%
“…That is, when there were more items to remember, all responses were slowed by a roughly constant amount. This pattern has also been observed for complex span tasks (Towse, Cowan, Hitch, & Horton, 2008). In a free recall task, Rohrer (1996) showed that the time taken to recall items increased substantially when the number of items in the study list increased from 8 to 16 words.…”
Section: Benchmarks For Working Memory 19supporting
confidence: 61%
“…Previous work has established that there are LTM contributions in what had been considered WM tasks (Cowan, 1988; Healy, Fendrich, Cunningham, & Till, 1987; Towse, Cowan, Hitch, & Horton, 2008; Unsworth & Engle, 2007; Waugh & Norman, 1965). For the present data set we have found it necessary to hypothesize that a fixed WM capacity can be supplemented by another mechanism that is not capacity-limited, in particular the activated portion of LTM (cf.…”
Section: Present Recognition Task and Its Contributionmentioning
confidence: 99%
“…Its contribution to working memory can be measured through recall item duration, that is, the time that elapses between the recall of two successive items. Unlike span length (i.e., the highest amount of information that children can recall accurately), recall durations offer direct insight on the temporal dynamic of memory search and recall processes and they correlate with academic achievement over and beyond span length (Cowan, 1992; Cowan et al, 1994, 1998, 2003; Towse, Cowan, Horton, & Whytock, 2008; Towse et al, 2008). Critically, the recall duration for the first item in the memorandum, that is, the preparatory interval, is longer than subsequent item recall durations in working memory span tasks during middle childhood and adulthood.…”
mentioning
confidence: 99%